THE DEMOGRAPHIC SITUATION INFLUENCE ON EPIDEMIOLOGY OF ACUTE CORONARY PATHOLOGY IN URBAN POPULATION OF THE WEST-SIBERIAN REGION - A. A. Garganeeva; S. A. Okrugin; K. N. Borel; E. A. Parshin (Российский кардиологический журнал)
Aim. To evaluate the changes in demographic situation influence on morbidity, mortality and lethality from acute myocardial infarction in Tomsk in 1984-2010 y.y. Material and methods. The study was done under the WHO program “Registry of acute myocardial infarction”. Epidemiology of infarction was studied among citizens older than 20 y.o. For the period studied there were 24850 cases of the disease registered. In the acute phase 9390 patients died, including 3314 (36,4%) inpatients and 6076 (64,7%) prehospital patients. Information on quantitative and age-gender properties of citizens was studied based on the data obtained in the regional statistics department.Results. During the study the demographic situation in the city was characterized by strong tendency to ageing of the population and to increase the part of older persons in the cohort. This factor led to the increase of morbidity and mortality of the city inhabitants from myocardial infarction, registered during the first years of the study. Negatively the ageing of the population influenced also the parameters of in-patient lethality. Prevalence of older persons among all patients led to the increase of severity of anamnestic background of infarction and the increase of atypical clinical flow of the disease (astmatic; abdominal; collaptoid etc.). This made difficulties for the disease diagnostics at prehospital stage and led to the increase the part of those who received treatment in non-specialized hospitals. High mortality in non-specialized hospitals was the reason that led to the mean lethality in the city. Ageing did not influence the prehospital lethality of Tomsk. However it should be mentioned that in age-related structure of the patients died in prehospital period, the part of older people was almost the same as in younger groups.Conclusion. So the ageing of the inhabitants led to the fact that Tomsk epidemiologic situation for myocardial infarction were dependent on the prevalence of this pathology among the citizens older than 60 y. The situation relevantly signs on the necessity of urgent healthcare system improvement for the patients with acute coronary pathology to the side of older age groups.